Orientasi Kewirausahaan dalam Kinerja UMKM di Jember - Enny Hindarwati; Agus Rahayu; Lili Adi Wibowo (University of Merdeka Malang, 2021)
The entrepreneurial orientation that affects the performance of Micro, Small and Medium Enterprises (MSMEs) in Jember is a research objective. The study population was 172 micro, small and medium enterprises in Jember. This research uses 100 respondents with simple random sampling technique. The research respondents were the owners of the MSME as informants. Collecting data by distributing questionnaires to 100 respondents. The collected data were analyzed using Structural Equation Modeling (SEM) Partial Least Square (PLS) software. The results showed that the autonomous dimension had a significant effect on the performance of MSMEs, while the other dimensions of entrepreneurial orientation: innovation, proactivity and risk had no significant effect.